LDM-PT - A Portuguese Lexicon of Discourse Markers - Mendes, Amália (2016)
The Lexicon of Discourse Markers (LDM-PT) provides a set of lexical items in Portuguese that have the function of structuring discourse and ensuring textual cohesion and coherence at intrasentential and inter-sentential levels. Each connective is associated to the set of its rhetorical senses, following the PDTB typology.